2003
DOI: 10.3121/cmr.1.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Ischemic Neuroprotection by Potentiators of Gamma-aminobutyric Acid

Abstract: INTRODUCTION

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Increasing GABA signalling in post stroke patients and rodent models does not improve motor function16. Rather, administering a benzodiazepine after rehabilitation leads to an acute loss of the regained function2474.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing GABA signalling in post stroke patients and rodent models does not improve motor function16. Rather, administering a benzodiazepine after rehabilitation leads to an acute loss of the regained function2474.…”
Section: Discussionmentioning
confidence: 99%
“…The GABAergic system and the extracellular matrix could have an important role in controlling plastic phenomena16. For example, Perineuronal Nets (PNNs), preferentially surrounding the soma of fast-spiking parvalbumin-positive interneurons17, and the GABAergic system have been extensively investigated during the maturation and plasticity of the visual system181920.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although in vitro studies of topiramate and lamotrigine have suggested a neuroprotective effect 29 , in vivo studies were generally negative in various models of focal cerebral ischemia 18-22 . All studies, however, have tested single doses or short-term treatment administered before or after ischemia onset.…”
Section: Discussionmentioning
confidence: 99%
“…We tested lamotrigine because it also inhibits SD upon chronic treatment in rats 16 , although its efficacy in migraine is not proven 17 . Both drugs have been studied previously in experimental focal ischemia models without consistent efficacy, albeit as a single dose or as short-term post-ischemic dosing 18-22 . Therefore, neither drug has been tested as a prophylactic intervention in stroke.…”
Section: Introductionmentioning
confidence: 99%